How can we improve on the current approaches to planning tourist precincts in small towns in South Africa? - De Jager, J. N. B. (University of the Free State, 2016)
Many small towns in South Africa are burdened with a legacy of poverty and unemployment. As a response to these social and urban issues this research project argues for an approach towards town planning in such a way as to promote sustainable pro-poor tourism . The research project aims to explore how a themed integrated resort development can be used as a tool to restructure the economy of Hazyview X44 and other similar small towns in South Africa. The research project presents a Site Development Plan for Hazyview X44, which includes an International Convention Centre ICC, Casino, Pre-Colonial Heritage museum, restaurants, hotel precinct, playpark and greenstone museum, which will potentially pave the way for future similar integrated resort developments in small towns in South-Africa. Hopefully these development nodes can act as a catalyst for economic revival not only in the tourism industry but also in its respective communities all over South-Africa. The intended outcome is that this Integrated Resort Development will be economically viable, socially just and ecologically sustainable.
Dissertation (M.U.R.P. (Urban and Regional Planning))--University of the Free State, 2016
Keywords: South Africa; Small towns; Tourism; Themed integrated resort development; Hazyview